The relationship between asthma and common mental health disorders: depression and anxiety disorders - Krupińska, Natalia; Marszałek, Kamil; Matysiak, Julia; Adamczewska, Magdalena (Alergologia Polska - Polish Journal of Allergology, 2026)
Asthma is a chronic, inflammatory respiratory disease characterised by reversible airflow limitation and airway hyperresponsiveness. It affects over 300 million people worldwide and has a negative impact on patients’ quality of life. Asthma is accompanied by various comorbidities, including common mental health disorders. Anxiety and depression are the most frequent among them, with a prevalence of 11–13%, and they are associated with poorer asthma control and reduced medication adherence. Anxiety disorders and depression are closely related due to shared elements in the pathogenesis of both conditions. The Global Initiative for Asthma highlights the significant prevalence and underdiagnosis of psychiatric conditions among individuals with asthma and points out the lack of a structured treatment plan for those with depression and anxiety due to insufficient data. The aim of this review is to analyse current studies on the correlation between asthma and common mental health disorders. It presents information on depression and anxiety disorders, their impact on asthma management, and outlines proposed psychiatric interventions for these comorbidities.